Investment attractiveness of Kazakhstani regions’ agriculture for companies from Republic of Korea - Смaгулов К.; Ем, Н. (Journal of Oriental Studies, 2017)
The study found that food security is a priority for Kazakhstan and Korea. At the same time, now the Kazakh government is implementing a set of measures to develop the agricultural sector. In turn, Korea is interested in the development of agriculture in foreign countries. This strategy of Seoul seeks to solve the problem of self-reliance. The most attractive regions for foreign investment in Kazakhstan are the South and North.